An Agent-Based Approach for a Smart Transport System - Peñaranda, Cristian; Aguero, Jorge; Carrascosa, Carlos; Rebollo, Miguel; Julián, Vicente (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2016)
This paper presents a proposal for a Smart Transport System which is an application that facilitates the interconnection between people (citizens, tourists) and transport providers (Bus, metro, trains, trams), defining the services that everyone can request or offer. The system has been defined as a virtual organization where agents (representing actors of the transport system) can enter or leave into the system consuming or offering services. Due to the fact that modern urban public transport is increasingly an important service used by citizens in current cities, the proposed system will improve the use of resources while also ensuring time flexible mobility solutions for citizens.